2019
DOI: 10.1080/17429145.2019.1662101
|View full text |Cite
|
Sign up to set email alerts
|

Improving plant growth and alleviating photosynthetic inhibition from salt stress using AMF in alfalfa seedlings

Abstract: The effects of arbuscular mycorrhizal fungi Glomus mosseae (+AMF) on the growth, nutrient uptake and leaf photosynthetic characteristics of alfalfa (Medicago sativa) under salt stress were studied. In alfalfa, 100 mM salt stress had no obvious effect on plant growth, nutrient content and photosynthetic capacity, however, 200 mM salt stress significantly inhibited biomass accumulation and NPK uptake. In addition, 200 mM salt stress led to decreased photosynthetic carbon assimilation capacity and lower PSII and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 72 publications
(72 reference statements)
2
13
0
Order By: Relevance
“…AMF inoculation was able to improve the gas exchange capacity of the L. chinensis seedlings most likely by maintaining stomatal opening, reducing stomatal resistances and increasing transpiration fluxes (Evelin et al 2019). Our results demonstrated that the positive effect of AMF on net photosynthetic rate improvement was associated with an increase in stomatal conductance resulted in a noticeable promotion in photosynthesis efficiency which is in line with reports by Shi-chu et al (2019). In this study, the improvement in leaf gas processes could be attributed to the increasing nutrient uptake, chlorophyll content and water use efficiency (WUE) caused by AMF inoculation (Figure 5 and Figure S2).…”
Section: Effects Of Amf Inoculation and Saline-alkaline Stress On Plasupporting
confidence: 92%
See 1 more Smart Citation
“…AMF inoculation was able to improve the gas exchange capacity of the L. chinensis seedlings most likely by maintaining stomatal opening, reducing stomatal resistances and increasing transpiration fluxes (Evelin et al 2019). Our results demonstrated that the positive effect of AMF on net photosynthetic rate improvement was associated with an increase in stomatal conductance resulted in a noticeable promotion in photosynthesis efficiency which is in line with reports by Shi-chu et al (2019). In this study, the improvement in leaf gas processes could be attributed to the increasing nutrient uptake, chlorophyll content and water use efficiency (WUE) caused by AMF inoculation (Figure 5 and Figure S2).…”
Section: Effects Of Amf Inoculation and Saline-alkaline Stress On Plasupporting
confidence: 92%
“…Although many studies have indicated the beneficial effects of AMF on salt stress alleviation in various plants (Shi-chu et al 2019;Tisarum et al 2020;Kong et al 2020), but the magnitudes of effect greatly differ among these studies. Simultaneously, the different impacts of AMF inoculation on the alleviation of salt stress have been also found in citrus seedlings with differential salinity tolerance (Navarro et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The use of AMF has been shown to be more advantageous for plant growth under salt stress, especially those inoculated with arbuscular mycorrhizal consortium (MC). Other studies of different crops as sweet basil (Elhindi et al 2017), alfalfa (Liang et al 2019), andSesban (Abd_Allah et al 2015) have reported that AMF can promote mineral nutrition uptake, which explains the improvement in plant growth by AMF inoculation under salt stress. The efficiency of MC might be due to the height compatibility relationships between species (Parihar et al 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Arbuscular mycorrhizal fungi enhance the chlorophyll content, PSII photochemical efficiency, and net photosynthetic rate of plants ( Wu and Xia, 2006 ; Zhu et al, 2014 ; AugĂ© et al, 2016 ; Shi-Chu et al, 2019 ) and also transfer plant photosynthates underground, which can stimulate PSB activity and growth ( Zhang et al, 2016 ) as most PSB are heterotrophic and depend on nutrient substrates that can be easily decomposed. AMF hyphae are also rapid channels for the recently produced photosynthates, which can attract PSB and promote their growth ( Kaiser et al, 2015 ).…”
Section: Synergistic Effects Of Amf Psb and Si On P Availabilitymentioning
confidence: 99%